2014
DOI: 10.1021/jp4116639
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Polarity Considerations Are Unable to Describe Fullerene Solvation Behavior

Abstract: Atomistic molecular dynamics simulations were employed to investigate the solvation properties of the fullerene C60 in binary water/dimethyl sulfoxide (DMSO) mixtures. Structural analysis indicates a preferential solvation with the predominance of DMSO molecules in the first solvation shell for the solutions with low concentrations of DMSO. PMF calculations indicate a maximization of the hydrophobic interaction at low concentrations of DMSO. The contact minima indicate a tendency of aggregation of these nanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…[44] Since the bonding occurred between DMSO and C 60 molecules, C 60 molecules that mixed with Sn x Pb 1-x I 2 Á xDMSO complexes were wrapped around by the DMSO molecules and formed solvent shells. [54] The presence of C 60 molecules increased surface energy and thus decreased grain sizes of PbI 2 /SnI 2 precursor thin films. Finally, C 60 molecules could tune the crystallization of MASn 0.25 Pb 0.75 I 3 perovskite films with decreased pinholes and uniformly disperse between grain boundaries.…”
Section: Two-step Solution-process Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Since the bonding occurred between DMSO and C 60 molecules, C 60 molecules that mixed with Sn x Pb 1-x I 2 Á xDMSO complexes were wrapped around by the DMSO molecules and formed solvent shells. [54] The presence of C 60 molecules increased surface energy and thus decreased grain sizes of PbI 2 /SnI 2 precursor thin films. Finally, C 60 molecules could tune the crystallization of MASn 0.25 Pb 0.75 I 3 perovskite films with decreased pinholes and uniformly disperse between grain boundaries.…”
Section: Two-step Solution-process Methodsmentioning
confidence: 99%
“…After investigated the influence of DMSO on the two‐process crystallization of Sn‐Pb binary perovskites, Mai and co‐workers further introduced C 60 into the precursor solution of mixed PbI 2 and SnI 2 . Since the bonding occurred between DMSO and C 60 molecules, C 60 molecules that mixed with Sn x Pb 1‐ x I 2 · x DMSO complexes were wrapped around by the DMSO molecules and formed solvent shells . The presence of C 60 molecules increased surface energy and thus decreased grain sizes of PbI 2 /SnI 2 precursor thin films.…”
Section: Crystallization Properties and Applications Of Low‐bandgapmentioning
confidence: 99%
“…This model has been successfully used in recent MD simulations of hydrating properties of pristine fullerenes/fullerene derivatives in aqueous medium or in binary water-containing solvents 36,[79][80][81][82][83][84][85][86][87] and in simulations of C 60complexes with biomacromolecules. 10,64,88,89 To obtain a start configuration, bare fullerene or amphiphilic molecule (and counterion if needed) in optimized geometry is placed in a cubic box and then solvated with n = 1000 or 3000 water molecules, which are uniformly and randomly distributed over the simulation box.…”
Section: Simulation Setup and Computed Propertiesmentioning
confidence: 99%
“…The behavior of fullerene (C 60 ) is closest to that of classical nonpolar molecules (this means that the molecule has an almost perfect spherical shape). Chaban et al showed an increasing tendency for fullerene aggregation in both binary solvent (water/DMSO) at any composition, and in either of the pure solvents. This is consistent with our studies, which used water as a solvent.…”
Section: Introductionmentioning
confidence: 99%